Proceedings of the FISITA 2012 World Automotive Congress Volume 13: Noise, Vibration and Harshness (NVH). (Lecture Notes in Electrical Engineering,, 2013)
Proceedings of the FISITA 2012 World Automotive Congress are selected from nearly 2,000 papers submitted to the 34th FISITA World Automotive Congress, which is held by Society of Automotive Engineers of China (SAE-China ) and the International Federation of Automotive Engineering Societies (FISITA). This proceedings focus on solutions for sustainable mobility in all areas of passenger car, truck and bus transportation. Volume 13: Noise, Vibration and Harshness (NVH) focuses on: •Chassis Vibration and Noise Control •Transmission Vibration and Noise Control •Engine Vibration and Noise Control •Body Vibration and Noise Control •Vehicle Vibration and Noise Control •Analysis and Evaluation of In-Car Vibration & Noise •Wind Noise Control Technology •Vibration and Noise Testing Technology Above all researchers, professional engineers and graduates in fields of automotive engineering, mechanical engineering and electronic engineering will benefit from this book.   SAE-China is a national academic organization composed of enterprises and professionals who focus on research, design and education in the fields of automotive and related industries. FISITA is the umbrella organization for the national automotive societies in 37 countries around the world. It was founded in Paris in 1948 with the purpose of bringing engineers from around the world together in a spirit of cooperation to share ideas and advance the technological development of the automobile.